A design of 2.5GHz sierpinski carpet fractal antenna for ISM band application / Amalina Syazwani Ahmad Suhami - Ahmad Suhami, Amalina Syazwani (2016)
This work proposes a design of Sierpinski Carpet Fractal Antenna (SCFA) operates at 2.5 GHz for ISM band application. Industrial, scientific and medical (ISM) radio bands are internationally reserved for use by industrial, scientific and medical equipment such as process heating, microwave oven and medical diathermy equipment. These devices were limited to certain bands of frequencies because the devices cause electromagnetic interference that may disrupt radio communication. The use of fractal geometry in antenna design can provides a good method for achieving the desired miniaturization and multiband properties. So the Sierpinski Carpet Fractal Antenna was chosen for ISM band application. The Sierpinski Carpet Fractal Antenna is designed and fabricated on FR-4 substrate, with dielectric constant of 4.3, copper thickness of 0.035 mm and substrate thickness of 1.6mm. This antenna is designed and simulated by software which is Computer Simulation Technology (CST) Microwave Studio Suite 2014. The fabricated antenna design is measured using vector network analyzer (VNA). The both results, simulation and measurement were observed and analyzed.